Antigen rapid diagnostic test monitoring for SARS‐CoV‐2 in asymptomatic and fully vaccinated cancer patients: Is it cost‐effective?. (30th December 2022) - Caccese, Mario; Saieva, Anna Maria; Guarneri, Valentina; Lonardi, Sara; Cacco, Massimo; Sileni, Vanna Chiarion; Gottardi, Michele; Mioranza, Eleonora; Bergamo, Francesca; Brunello, Antonella; Zagonel, Vittorina; Benini, Patrizia
Abstract: Background: Routine testing for cancer patients not presenting COVID‐19‐related symptoms and fully vaccinated for SARS‐CoV‐2 prior to cancer treatment is controversial. Methods: In this retrospective study we evaluated whether antigen‐rapid‐diagnostic‐test (Ag‐RDT) monitoring for SARS‐CoV‐2 in a large cohort of consecutive asymptomatic (absence of SARS‐CoV‐2‐related symptoms such as fever, cough, sore throat or nasal congestion) and fully vaccinated cancer patients enrolled in a short period during cancer treatment has an impact on the therapeutic path of cancer patients. Results: From December 27, 2021, to February 11, 2022, 2439 cancer patients were screened through Ag‐RDT for SARS‐CoV‐2 before entering the hospital for systemic treatment. Fifty‐three patients (2.17%) tested positive, of whom 7 (13.2%) subsequently developed COVID‐related symptoms, generally mild. Cancer treatment was discontinued, as a precaution, in 49 patients (92.5%) due to the test positivity. Conclusion: SARS‐CoV‐2 screening in asymptomatic and fully vaccinated cancer patients during systemic treatment appeared to be not cost‐effective: the low rate of SARS‐CoV‐2 positive patients and the low percentage of overt associated infection do not seem proportional to the direct costs (nursing work for swabs, costs of materials and patient monitoring) and indirect costs (dedicated rooms, extension of waiting times for patients and oncologists in delivering therapy as well as its discontinuation in the positive ones). It can, on the other hand, be detrimental when systemic cancer treatment is suspended as a precaution. Given the small number of patients testing positive and the rapid and favorable trend of the infection, it is recommended to always consider continuing systemic oncological treatment, especially when this impacts patient survival as in the adjuvant or neoadjuvant setting. Abstract : SARS‐CoV‐2 screening in asymptomatic and fully‐vaccinated cancer patients during systemic treatment appeared to be not cost‐effective.